Predicting information security culture among employees of telecommunication companies in an emerging market - Md Azmi, Nurul Asmui Azmi; Teoh, Ai Ping; Vafaei-Zadeh, Ali; Hanifah, Haniruzila (Information and computer security, 2021)
PurposeThe purpose of this study is to examine factors, which influence information security culture among employees of telecommunications companies. The motivation for this study was the rise in the number of data breach incidents caused by the organizations’ own employees.Design/methodology/approachA total of 139 usable responses were collected via a Web-based questionnaire survey from employees of Malaysian telecommunications companies. Data were analysed by using SmartPLS 3.FindingsSecurity education, training and awareness (SETA) programmes and information security awareness were found to have a positive and significant impact on Information Security Culture. Additionally, self-reported employees’ security behaviour was found to act as a partial mediator on the relationship between information security awareness and information security culture.Research limitations/implicationsThe study was cross-sectional in nature. Therefore, it could not measure changes in population over time.Practical implicationsThe empirical data provides a new perspective on significant elements that influence information security culture in an emerging market. Organizations in the telecommunications industry can now recognize that SETA programmes and information security awareness have a significant impact on information security culture. Employees’ security behaviour also mediates the relationship between information security awareness and information security culture.Originality/valueThis is the first study to analyse the mediating effect of employees’ security behaviour on the relationship between information security awareness and information security culture in the Malaysian telecommunications context.